PUF60-activated exons uncover altered 3' splice-site selection by germline missense mutations in a single RRM - Královicová, Jana; Ševcíková, Ivana; Stejskalová, Eva; Obuca, Mina; Hiller, Michael; Stanek, David; Vorechovský, Igor (Nucleic acids research, 2018)
PUF60 is a splicing factor that binds uridine (U)-rich tracts and facilitates association of the U2 small nuclear ribonucleoprotein with primary transcripts. PUF60 deficiency (PD) causes a developmental delay coupled with intellectual disability and spinal, cardiac, ocular and renal defects, but PD pathogenesis is not understood. Using RNA-Seq, we identify human PUF60-regulated exons and show that PUF60 preferentially acts as their activator. PUF60-activated internal exons are enriched for Us upstream of their 3' splice sites (3'ss), are preceded by longer AG dinucleotide exclusion zones and more distant branch sites, with a higher probability of unpaired interactions across a typical branch site location as compared to control exons. In contrast, PUF60-repressed exons show U-depletion with lower estimates of RNA single-strandedness. We also describe PUF60-regulated, alternatively spliced isoforms encoding other U-bound splicing factors, including PUF60 partners, suggesting that they are co-regulated in the cell, and identify PUF60-regulated exons derived from transposed elements. PD-associated amino-acid substitutions, even within a single RNA recognition motif (RRM), altered selection of competing 3'ss and branch points of a PUF60-dependent exon and the 3'ss choice was also influenced by alternative splicing of PUF60. Finally, we propose that differential distribution of RNA processing steps detected in cells lacking PUF60 and the PUF60-paralog RBM39 is due to the RBM39 RS domain interactions. Together, these results provide new insights into regulation of exon usage by the 3'ss organization and reveal that germline mutation heterogeneity in RRMs can enhance phenotypic variability at the level of splice-site and branch-site selection.
Keywords: Repressor Proteins; malý jaderný ribonukleoprotein U1; lidé; RNA Splicing Factors; HeLa Cells; Ribonucleoprotein, U1 Small Nuclear; krátké rozptýlené jaderné elementy; Short Interspersed Nucleotide Elements; místa sestřihu RNA; Amino Acid Motifs; represorové proteiny; RNA Splice Sites; RNA-Binding Proteins; Heterogeneous-Nuclear Ribonucleoproteins; Mutation, Missense; Humans; Sequence Analysis, RNA; Splicing Factor U2AF; HEK293 buňky; sestřihový faktor U2AF; jaderné proteiny; HeLa buňky; missense mutace; exony; proteiny vázající RNA; aminokyselinové motivy; sestřihové faktory; heterogenní jaderné ribonukleoproteiny; Exons; sekvenční analýza RNA; HEK293 Cells; Nuclear Proteins